Enhancing Guest Satisfaction Through Service Leadership, Customer Relationship Management, and Employee Engagement in Luxury Hotels in Bangkok and Yangon - Oo, Htet Nanddar; Batra, Adarsh; Barnes, John (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Growing competition in the hotel industry demands enhanced customer relationship management, employee engagement, and service leadership. This study investigates the importance of service leadership, CRM techniques, and employee engagement on guest satisfaction in selected hotels located in Bangkok and Yangon. Key findings from interviews conducted with ten participants across four luxury hotels revealed that CRM-enabled individualized guest services, service leadership, and employee engagement, significantly contribute to enhancing guest satisfaction. The study highlights the crucial role of CRM and employee engagement in managing interactions with guests and suggests strategies for increasing employee engagement. These insights provide strategies for maintaining a competitive edge in the rapidly evolving hospitality industry and fostering long-term guest satisfaction.